Phenomenological Insights into Small Talk: A Co-Cultural Analysis of Chinese Graduate Students in Canada - Hui Xu (Canadian Journal for New Scholars in Education)
Research shows that informal social interaction and engagement with peers and instructors play an important role in the academic success and mental well-being of international students. Small talk, a significant component of social interaction, poses a special challenge for those who use a second or additional language. Based on data from a phenomenological study which investigated challenges faced by Chinese graduate students in Canada, this paper uses co-cultural communication theory to explore the unique communicative strategies employed by three study participants who encountered ongoing problems with small talk in English. It was found that all three followed the same communicative orientation: non-assertive separation and adopted similar communicative strategies: avoiding, maintaining barriers, and leaving the situation. It is recommended that educational environments that embrace and value various communicative norms should be encouraged to support international students.